A halogen bond-donor amino acid for organocatalysis in water. Issue 76 (6th September 2018) - Bergamaschi, Greta; Lascialfari, Luisa; Pizzi, Andrea; Martinez Espinoza, Maria Isabel; Demitri, Nicola; Milani, Alberto; Gori, Alessandro; Metrangolo, Pierangelo
Abstract : An XB-donor amino acid compoundF(F4 I) effectively promotes homogeneous catalysis of condensation reactions in water. Abstract : Herein we report a halogen bond-donor amino acid, 4-iodotetrafluorophenylalanine, which behaves as a catalyst for the aqueous synthesis of bis-(heterocyclic)methanes. We also provide experimental evidence that halogen bonding is a plausible explanation for the observed catalytic effect.